1975
DOI: 10.1159/000208156
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin Stanleyville II (<i>α</i> 78 [EF 7] Asn → Lys) Found in France

Abstract: Haemoglobin Stanleyville II has been found several times in individuals from Central Africa.S This paper now reports its discovery in Alsace, in a family of long-standîng local ancestry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“… N.A. [ 12 ] Hb Stanleyville-II French 6 Normal Normal 24 [ 36 ] Hb Stanleyville-II Caucasian 1 11.0 88 15.3 This report Hb Stanleyville-II African 1 14.1 90 11.1 42.7 This report p.D94N (c.283G>A) Hb Titusville Swedish/Finish 1 13.3 91 15.6 1.13 [ 37 ] Hb Titusville Swedish/Finish 1 13.6 88 16 [ 37 ] Hb Titusville Scottish 1 15.8 85.9 17 [ 38 ] Hb Titusville Scottish 1 14.5 91 11 [ 38 ] Hb Titusville Scottish 1 Normal Normal 14 …”
Section: Methodsmentioning
confidence: 99%
“… N.A. [ 12 ] Hb Stanleyville-II French 6 Normal Normal 24 [ 36 ] Hb Stanleyville-II Caucasian 1 11.0 88 15.3 This report Hb Stanleyville-II African 1 14.1 90 11.1 42.7 This report p.D94N (c.283G>A) Hb Titusville Swedish/Finish 1 13.3 91 15.6 1.13 [ 37 ] Hb Titusville Swedish/Finish 1 13.6 88 16 [ 37 ] Hb Titusville Scottish 1 15.8 85.9 17 [ 38 ] Hb Titusville Scottish 1 14.5 91 11 [ 38 ] Hb Titusville Scottish 1 Normal Normal 14 …”
Section: Methodsmentioning
confidence: 99%
“…, 1975; Lorkin et al. , 1975); Hb Stanleyville‐II has been reported in families of African ethnic origin from the Congo, Uganda, Zaire, Texas (USA), and Alsace (France) (Van Ros, Beale & Lehmann, 1968; North et al. , 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Four other a-chain variants with a similar phenotype to Hb G-Philadelphia were identified by DNA sequencing: Hb G-Norfolk, Hb Stanleyville-II, Hb Matsue-Oki and Hb Mizushi. Hb G-Norfolk has been found in a few English families in England and Canada (Cohen-Solal et al, 1975;Lorkin et al, 1975); Hb Stanleyville-II has been reported in families of African ethnic origin from the Congo, Uganda, Zaire, Texas (USA), and Alsace (France) (Van Ros, Beale & Lehmann, 1968;North et al, 1975). Hb Matsue-Oki is reported to be found in a few Japanese and families of Arican ethnic origin (Ohba et al, 1977;Moo-Penn, Johnson & Therrell, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Bearers of Hb Stanleyville II are clinically normal. Hb Stanleyville II is not uncommon in some regions of Africa, but has only once been reported in a family of European descent (5 ). The index patient is of German origin.…”
Section: Tion (8 )mentioning
confidence: 96%